The Philippine Disaster Risk Reduction and Management in Health: A Sequential Explanatory Approach - Hermosura, Mary Joy; Decendario, Aaron Carlo; Chiong, Leo (Journal of Interdisciplinary Perspectives, 2025)
Despite being mandated and operational in the Philippines, there is a critical gap in a standardized, context-specific, and evidence-based framework to guide the nationwide consistent, coordinated, and effective implementation of disaster risk reduction and management in health (DRRM-H) practices. Existing initiatives are often fragmented, vary widely across regions, and lack an integrated structure that aligns mitigation and prevention, preparedness, response, rehabilitation, and recovery activities in the health sector. To address this gap, the study aimed to develop a framework by identifying and analyzing current practices and best practices in DRRM-H. A mixed-methods explanatory sequential design was employed, combining quantitative and qualitative approaches. In the quantitative phase, 30 DRRM-H managers were surveyed using a validated questionnaire, revealing that all DRRM-H practices were implemented to a high extent. In the qualitative phase, focus group discussion with 7 DRRM-H managers generated four major themes of best practices: (a) strengthening disaster mitigation through inclusive, data-driven strategies, partnerships, and culturally adaptive management; (b) institutionalizing disaster programs through governance, capacity building, and multi-sectoral collaboration; (c) ensuring coordinated and adaptive disaster response for efficient health and social service delivery; and (d) promoting resilient and collaborative post-disaster recovery efforts for sustainable community rebuilding. These findings informed the development of the Hermosura DRRM-H Framework, which provides a systematic and integrated approach to strengthening all phases of disaster management within the health sector. The study concludes that addressing the fragmentation through a unified framework is essential for enhancing DRRM-H program outcomes and recommends that the Health Emergency Management Bureau (HEM-B) collaborate with Regional DRRM-H Offices to implement regular program evaluations and research to sustain national alignment and responsiveness.